2017
DOI: 10.1007/s12602-017-9255-0
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum as a Probiotic Potential from Kouzeh Cheese (Traditional Iranian Cheese) and Its Antimicrobial Activity

Abstract: The aim of this study is to isolate and identify Lactobacillus plantarum isolates from traditional cheese, Kouzeh, and evaluate their antimicrobial activity against some food pathogens. In total, 56 lactic acid bacteria were isolated by morphological and biochemical methods, 12 of which were identified as Lactobacillus plantarum by biochemical method and 11 were confirmed by molecular method. For analyzing the antimicrobial activity of these isolates properly, diffusion method was performed. The isolates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…Actividad antimicrobiana.- Jabbari et al (2017), encontraron algunas cepas de Lactobacillus plantarum que no muestran actividad antimicrobiana contra E. coli y en algunos casos el halo fue más pequeño que otros patógenos. Por su parte Saxelin (1997), señala que determinadas cepas de lactobacilos tienen actividad antimicrobiana contra Salmonella y E. coli, sin embargo, en el presente estudio la cepa 7(1) inhibió a dos cepas patógenas de E. coli (ATCC25922 y ATCC35218)…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Actividad antimicrobiana.- Jabbari et al (2017), encontraron algunas cepas de Lactobacillus plantarum que no muestran actividad antimicrobiana contra E. coli y en algunos casos el halo fue más pequeño que otros patógenos. Por su parte Saxelin (1997), señala que determinadas cepas de lactobacilos tienen actividad antimicrobiana contra Salmonella y E. coli, sin embargo, en el presente estudio la cepa 7(1) inhibió a dos cepas patógenas de E. coli (ATCC25922 y ATCC35218)…”
Section: Discussionunclassified
“…Este lactobacilo es considerado como probiótico GRAS (GenBank YJ Jin-2018) y actualmente se está utilizando en alimentos para humanos y animales (Rodríguez 2009). Jabbari et al (2017) aislaron Lactobacillus plantarum con características probióticas de queso tradicional, esta bacteria es la más utilizada para la producción de alimentos fermentados. Por lo tanto, esta bacteria al tener 100% de similaridad con Lactobacillus plantarum subsp.…”
Section: Discussionunclassified
“…Streptococci was carried out based on biochemical characteristics in microbiology protocols [23,24]. Molecular analyses of lactobacilli species were done by method previously described [25,26]. To culture Enterococci spp., blood agar containing sheep blood was used at 37°C.…”
Section: Data Collectionmentioning
confidence: 99%
“…The other advantage of LAB is their non-toxic effects (Carr et al, 2002;Cotter et al, 2005). A total of 56 LAB were isolated by Jabbari et al (2017) and 12 of them were identified by using biochemical methods and 11 were identified using molecular method. Antimicrobial activity tests were performed using disc diffusion method and Staph.…”
Section: Introductionmentioning
confidence: 99%